Effect of Arsenic in Three Wheat Varieties of Bangladesh - Asaduzzman, Md.; Hossain, M. M.; Masum, S. M. (International Journal of Bio-resource and Stress Management, 2010)
A pot experiment was conducted in net house of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period from November, 2009 to February, 2010 to study the effect and accumulation of arsenic in three popular wheat varieties in Bangladesh. Three wheat varieties (V1=Protiva, V2=Sourav and V3=Gourav) and five levels of arsenic (As0=0, As10=10, As20=20, As30=30, As40=40 ppm kg-1 soil) were used in the experiment. The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Result showed that addition of arsenic significantly (p<0.05) reduced the growth, yield parameters and seed yield of wheat varieties. However, Gourav showed the potentiality against the arsenic toxicity up to 30 ppm arsenate salt kg-1 soil followed by Sourav and Protiva. The maximum plant height (100 cm), tillers hill-1(6), grain spike-1 (47), test weight (46 g), seed yield (4.51 t ha-1) but the lowest maturity days (104) was harvested in V3As0. Separately the lowest plant height (87.33 cm), tillers hill-1(4.33), grain spike-1 (36.33), test weight (41.00 g) but maximum maturity days (114) and yield reduction (5.987% compared to control) was recorded in V1As40. Arsenic concentration in plant parts increased with increasing the arsenate concentration in soil. Plant tissues were susceptible in the order of root>straw>grain and the concentrations of arsenic were dependent on variety and treatment levels in polluted soils and statistically (p<0.01) maximum concentration of arsenic in root (3.08 μg g-1), straw (0.9233 μg g-1) and grain (0.16 μg g-1) were measured in Protiva variety when it was cultivated with 40 ppm arsenic kg-1 soil. On the contrary, Gourav contained significantly (p<0.01) less amount arsenic in root (2.34 μg g-1), straw (0.376 μg g-1) and grain (0.04 μg g-1) at the same level of arsenic contaminated soil.